2018
DOI: 10.3727/096504018x15149761920868
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 Promotes Migration and Invasion of Lung Cancer Cells

Abstract: Lung cancer is the leading cause of cancer deaths worldwide. Given that the major threat of cancer is metastasis, delineation of the molecular mechanism underlying it would help devise therapeutic strategies. Transglutaminase 2 (TG2), belonging to the transglutaminase superfamily, is a versatile protein with enzymatic and nonenzymatic functions. It mainly localizes inside the cell, but also appears extracellularly. Recent findings have demonstrated the involvement of TG2 in cancer development. Here we examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Transglutaminase 2 (TGM2) exerts multiple physiological functions and is associated with cancer cell survival and metastatic behavior (36). It has been reported that TGM2 promotes the migration and invasion of lung cancer cells (37). The expression of PTGIS was found to be correlated with lung cancer patient survival (38).…”
Section: Discussionmentioning
confidence: 92%
“…Transglutaminase 2 (TGM2) exerts multiple physiological functions and is associated with cancer cell survival and metastatic behavior (36). It has been reported that TGM2 promotes the migration and invasion of lung cancer cells (37). The expression of PTGIS was found to be correlated with lung cancer patient survival (38).…”
Section: Discussionmentioning
confidence: 92%
“…On normal status, TG2 is predominantly located in cytoplasm, even there is some located in the nucleus, the mitochondria, on the plasma membrane, or in the extracellular cell surface (31, 32). Extracellular TG2 is mainly involved in wound healing and scarring, tissue fibrosis and cancer metastasis (33).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we hope to have emphasized that statement and encouraged consideration of moonlighting redox-regulated proteins as key players in deciding cellular fate under oxidative stress. CypA, TG2, CLIC (mentioned within the Transglutaminase 2 section), and DJ-1 are all associated with increased invasion and metastasis of cancer cells (133,138,197,422), with both DJ-1 and CypA exerting their influence through the regulation of kinase pathways (133,422). As cancer cells tend to block mitochondrial apoptotic induction, developments in cancer therapeutics often target the mitochondrial apoptosis signaling pathway, for example at p53 or the mPTP (105), and a direct link has been established between redox regulation of p53 and tumor progression (323).…”
Section: Fig 12 Ask1 Regulation By Both Antioxidant Enzymes and Moomentioning
confidence: 99%